Hubungan Faktor-Faktor Penyebab Kejadian Kutu Rambut pada Pondok Pesantren Al-Mubarok 2024 - Heny Sasmita; Erma Noor Wahyuningsih; Ucu Wandi Somantri; Siti Nur Ramdaniati; Lambang Satria Himawan; E. Egriana Handayani; Putu Eka Meiyana Erawan (Jurnal Sains dan Kesehatan, 2024)
The problem of pediculos capitis is a health problem that is still ignored by many people because it does not cause death, but the disease caused by pediculos capitis is very disturbing and can cause diseases such as: anemia, relapsing fever and others, The purpose of this study is to determine the relationship between direct and indirect risk factors to the incidence of Pediculos capitis in students at Al Mubarok Islamic boarding school, Serang, Banten in 2024, the type of research used is quantitative with a cross sectional design, The results of the analysis showed the results of statistical tests between the relationship between the incidence of pediculos capitis and doing activities together having (p value = 0.001 OR= 18.667), sleeping in one bed (p value = 0.003 OR= 4.420), exchanging hair combs (p value = 0.002 OR= 3.51), washing hair (p value = 0.000 OR= 5.275), exchanging veils (p value = 0.001). OR= 5,806). This capeculosis infection can be overcome jointly between health workers, the manager of the Al'Mubarok Islamic boarding school and the students in order to eliminate the problem of capeculosis infection in the Al'Mubarok Islamic boarding school.